PENGARUH DANA DESA DAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) TERHADAP TINGKAT KEMISKINAN DI PROVINSI ACEH - Muliza Muliza (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2022)
This study aims to see the effect of Village Fund and Gross Domestic Regional Product on poverty in districts / cities in Aceh Province during the 2017-2019 period. To analyze the data, the method used is panel data regression analysis with the estimation of model parameters using a fixed effect model (FEM). The results showed that the village funds variable did not have a significant effect on poverty, this happened because most of the village funds were allocated more to the infrastructure development sector, causing village funds to still not have a direct effect on reducing poverty. The Gross Domestic Regional Product variable has a negative but significant effect on poverty in the District / City of Aceh Province, which means that with an increase in Gross Domestic Regional Product it will significantly affect the reduction of poverty levels in Aceh Province.